Za dyplomem? Migracje młodych Polaków do miast akademickich - Datko, Anna (Człowiek i Społeczeństwo, 2014)
The 21st century is an age of mobility. Young Poles have also adapted to this trend – they migrate both abroad and within the confines of their own country. In the paper the author presents the migration to Polish academic cities, to which people arrive because of beginning their studies. But they do not only want to graduate from a university. Moving from their hometown entails too some bigger aims, such as launching a successful professional career, or staying and living in a big city and in consequence being a member of the metropolitan middle class. Academic education is considered due to its usefulness in gaining these aims (through the instrumental role of higher education) – and studies are more and more only a legitimization of a permanent migration to a metropolis.